Submesoscale fronts in the antarctic marginal ice zone and their response to wind forcing - Swart, S; Du Plessis, MD; Thompson, AF; Biddle, LC; Giddy, I; Linders, T; Mohrmann, M; Nicholson, Sarah-Anne (Geophysical Research Letters, 2020)
Submesoscale flows in the ocean are energetic motions, O(1–10 km), that influence stratification and the distributions of properties, such as heat and carbon. They are believed to play an important role in sea-ice-impacted oceans by modulating air-sea-ice fluxes and sea-ice extent. The intensity of these flows and their response to wind forcing are unobserved in the sea-ice regions of the Southern Ocean. We present the first submesoscale-resolving observations in the Antarctic marginal ice zone (MIZ) collected by surface and underwater autonomous vehicles, for >3 months in austral summer. We observe salinity-dominated lateral density fronts occurring at sub-kilometer scales. Surface winds are shown to modify the magnitude of the mixed-layer density fronts, revealing strongly coupled atmosphere-ocean processes. We posture that these wind-front interactions occur as a continuous interplay between front slumping and vertical mixing, which leads to the dispersion of submesoscale fronts. Such processes are expected to be ubiquitous in the Southern Ocean MIZ. 10 ©2020. The Authors. This is an open access article under the terms of the Creative Commons AttributionNonCommercialNoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is noncommercial and no modifications or adaptations are made Smart Places Ocean Systems and Climate